Cross-cultural research on cognitive development in infancy and early childhood: an overview of methods and research - SAADI, Hacène (Journal of Human Sciences, 2000)
In the present article, the author attempts to cover the most conspicuous studies and research in the area of cognitive development in infancy and early childhood across cultures, in the last thirty years or so. Studies of infants' attention and perception, object permanence and cognitive functioning, in general, in early childhood are discussed in relation to theoretical and methodological backgrounds (Piagetian studies, psychometric tests).In so doing, the author points out all through the paper, the complexity of multicultural research in terms of the difficulty of implementing research hypotheses, which may or may not be conclusive on dimensions of cognitive development.